18F‐Fluoroestradiol PET in the evaluation of probable oligometastatic breast cancer. Issue 3 (26th December 2020) - Denton, Matthew; Taubman, Kim; Sutherland, Tom
Summary: Recent advances with specific PET tracer ligands, for example prostate‐specific membrane antigen (PSMA)‐based PET imaging, have substantially improved the sensitivity and specificity of PET imaging. 18F‐Fluoroestradiol (FES) is a novel PET tracer that has been demonstrated to have high specificity for oestrogen receptor (ER) in breast cancer. This case describes the use of FES‐PET to further characterise a solitary scapular lesion in a patient with locally advanced ER‐positive breast cancer. In demonstrating FES avidity in the lesion, it was determined to represent metastatic disease, thus avoiding further biopsy with its associated morbidity. This case demonstrates the potential diagnostic utility of FES PET‐CT in the management of ER‐positive breast cancer patients with probable oligometastatic disease.